2022
DOI: 10.1002/ca.23840
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary surgical management of skull base chordomas—Anatomical reflections on a single center experience retrospective case series

Abstract: Chordoma, a rare, locally aggressive tumor can affect the central skull base, usually centered at the midline. Complete surgical resection remains mainstay of therapy in case of primary as well as recurrent tumors. Owing to their secluded location, surgical resection of skull base chordomas remains a challenge, even though the recent advancement of endoscopic endonasal approaches has had a significant positive impact on the management of these patients. Endoscopic endonasal approaches have been shown to signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…EEA is increasingly employed for CVJ chordoma resection as technique modifications have allowed for more lateral exposures. 11,37,[49][50][51][52] EEA establishes a corridor to the ventral brainstem unobstructed by cranial nerves or the vertebral arteries and minimizes brain retraction. 49 Based on their cadaveric study, Little et al demonstrated that en-doscopic endonasal clivectomy does not generate significant OC instability.…”
Section: Discussionmentioning
confidence: 99%
“…EEA is increasingly employed for CVJ chordoma resection as technique modifications have allowed for more lateral exposures. 11,37,[49][50][51][52] EEA establishes a corridor to the ventral brainstem unobstructed by cranial nerves or the vertebral arteries and minimizes brain retraction. 49 Based on their cadaveric study, Little et al demonstrated that en-doscopic endonasal clivectomy does not generate significant OC instability.…”
Section: Discussionmentioning
confidence: 99%